Neural Control of Cardiovascular Function During Exercise in Hypertension - Dombrowski, Maryetta; Mannozzi, Joseph; O’Leary, Donal S. (Frontiers in Physiology, 2018)
During dynamic exercise, hypertensive subjects can experience robust increases in arterial pressure and cardiac dysfunction to such an extent that heavy exercise is often not recommended in these patients due to the dangerously high levels of blood pressure sometimes observed. Currently, the mechanisms mediating this cardiovascular dysfunction during dynamic exercise in hypertension are not fully understood. The major reflexes thought to mediate the cardiovascular responses to exercise in normal subjects are central command, arterial baroreflex, and responses to stimulation of skeletal muscle mechano-sensitive and metabo-sensitive afferents. This review will summarize our current understanding of the roles of these reflexes and their interactions in mediating the altered cardiovascular responses to exercise observed in hypertension. We conclude that much work is needed to fully understand the mechanisms mediating excessive pressor response to exercise often seen in hypertensive patients.